Pengembangan Media Smart Box Literasi untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas II Sekolah Dasar - Lunissa Prasdiana Putri; Karimatus Saidah; Frans Aditia Wiguna (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Early reading instruction for Grade IIA students at MIS Al Irsyad Al Islamiyyah, Kediri City, has not been optimal due to a teacher-centered approach and limited use of instructional media. This study aims to determine the validity, practicality, and effectiveness of the